2019
DOI: 10.1101/2019.12.17.880229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual Orexin and MCH neuron-ablated mice display severe sleep attacks and cataplexy

Abstract: SummaryOrexin/hypocretin-producing and melanin-concentrating hormone-producing (MCH) neurons are co-extensive in the tuberal hypothalamus and project throughout the brain to regulate sleep/wakefulness. Ablation of orexin neurons in mice decreases wakefulness and results in a narcolepsy-like phenotype, whereas ablation of MCH neurons increases wakefulness. Since it is unclear how orexin and MCH neurons interact to regulate sleep/wakefulness, we generated conditional transgenic m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the silence of the MCH neurons during cataplexy implicates that their appropriate activation may inhibit cataplexy. Indeed, a recent study demonstrated that ablating both orexin and MCH neurons worsens cataplexy, revealing the possible role of MCH neurons in preventing cataplexy (Hung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the silence of the MCH neurons during cataplexy implicates that their appropriate activation may inhibit cataplexy. Indeed, a recent study demonstrated that ablating both orexin and MCH neurons worsens cataplexy, revealing the possible role of MCH neurons in preventing cataplexy (Hung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%